Histological Changes of Cartilage Degeneration in Osteoarthritic Rabbits - Svätoslav Hluchý (Scientific Papers Animal Science and Biotechnologies, 2023)
The objective of this research was to evaluate the effect of glucosamine sulfate on histological changes of articular cartilage degeneration in rabbits. Knee joints during development of osteoarthritis in rabbits following collagenase-induced osteoarthritis were investigated. A total of 32 New Zealand White male and female rabbits were used in this study. All animals were kept in standard conditions at Research Institute of Livestock Production in Nitra. Animals were divided into 4 groups: healthy control group, osteoarthritic untreated group and two experimental groups. After collagenase-induced osteoarthritis daily oral administration of glucosamine sulfate (80 mg.kg-1 and 160 mg.kg-1 of live weight) was performed. After completion of the experiment, rabbits were subjected to euthanasia. After euthanasia, femur and fibula together were dissected for morphological and histological examination. Histopathological degeneration was assessed from histological slides. All parameters evaluated in osteoarthritic groups have specific stage of development of osteoarthritis, thickening of cartilage surface, cartilage thickness, number and distribution of chondrocytes and overall morphology. Morphological and histological evaluation of the femoral condyles in glucosamine-treated groups showed a lower extent and severity of the destruction of the cartilage in comparison with osteoarthritic control group.